1996
DOI: 10.1002/(sici)1097-0215(19960117)65:2<221::aid-ijc16>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The murine Fc-gamma (Fcγ) receptor type II B1 is a tumorigenicity-enhancing factor in polyoma-virus-transformed 3T3 cells

Abstract: o 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…In our previous work, we observed that the expression of FcγRIIB in human melanoma was associated to inhibition of tumor development in nude mice and increased the therapeutic effect of anti‐tumor IgG in SCID mice 26. These observations are in apparent contradiction with our current results and previous studies showed that FcγRIIB1 expressed by polyoma‐virus‐transformed nonhematopoietic tumor confers an in vivo growth advantage to tumor cells and increases their malignancy when grafted subcutaneously in immunocompetent mice 36. One hypothesis to explain this discrepancy can be the different nature of the antibodies that mediate the anti‐tumor defenses in these studies.…”
Section: Discussioncontrasting
confidence: 98%
“…In our previous work, we observed that the expression of FcγRIIB in human melanoma was associated to inhibition of tumor development in nude mice and increased the therapeutic effect of anti‐tumor IgG in SCID mice 26. These observations are in apparent contradiction with our current results and previous studies showed that FcγRIIB1 expressed by polyoma‐virus‐transformed nonhematopoietic tumor confers an in vivo growth advantage to tumor cells and increases their malignancy when grafted subcutaneously in immunocompetent mice 36. One hypothesis to explain this discrepancy can be the different nature of the antibodies that mediate the anti‐tumor defenses in these studies.…”
Section: Discussioncontrasting
confidence: 98%
“…One such microenvironment-induced molecule with the capacity to confer a high malignancy phenotype upon mouse tumor cells was identified in our laboratory as an immunoglobulin receptor, the Fc-y receptor type lIB 1 (Ran et al, 1992;Zusman et al, 1996a and1996b). In an unpublished study, we identified the factor capable of inducing the expression of the Fc receptor to be an interferon-y, a cytokine known to be present in the microenvironment of several cancer types (Hess et aI., 2003;Lebel-Binay et aI., 2003).…”
mentioning
confidence: 86%
“…The work in our laboratory focuses on tumor-CMF interactions trying to identify genes whose expression is altered (induced/upregulated or silenced/downregulated) by CMF-mediated signaling as low malignancy tumor cells progress to a high malignancy phenotype [Zusman et al, 1996a;Katz et al, 1994Katz et al, , 1994Katz et al, -1995Witz et al, 1996;Halachmi and Witz, 1989;Ben-Baruch et al, 1992;Ran et al, 1991]. The approach undertaken has been to screen for microenvironmentregulated gene-products differentially expressed by tumor cells expressing either a high or a low malignancy phenotype [Katz et al, 1994;Witz et al, 1996;Halachmi and Witz, 1989].…”
Section: Microenvironment-regulated Genes and The Involvement Of Murimentioning
confidence: 99%
“…A comprehensive comparison in gene expression profiles of nonmetastatic and metastatic tumor cells has not been constructed as yet. However, numerous studies focusing on certain gene products that are likely to play a role in tumor progression toward metastasis have demonstrated differences in their expression between less and more progressed tumor cells [Zhang et al, 1997;Zusman et al, 1996a;Katz et al, 1994;Fidler et al, 1996;Witz et al, 1996]. Because tumor progression toward metastasis largely involves genes that control the social behavior of cancer cells such as adhesion, motility, invasiveness, and interaction with growth factors [Hakomori, 1996], these genes should be focused on.…”
mentioning
confidence: 99%